When you are near [large type] - Peterson, Tracie (Peterson, Tracie. Brookstone brides, 2019)
1900. Lizzy Brookstone, star trick rider of the all-female Brookstone Wild West Extravaganza, takes over management of the traveling show after her father's death. Working with Wesley DeShazer, the man who once broke her heart, and Jason Adler, her financial partner, she is soon torn between the two men. Ella Fleming, fleeing a forced betrothal, stows away on the train and is given a job in the costume department. Mary Reichert, a former sharpshooter for the show, refuses to believe the death of her brother, August, was an accident and returns to the show for the truth. As the train travels coast to coast, they must work together to save the show-- and each other.